Atrial Fibrillation Mechanisms and Treatment - Liu, Tong (IntechOpen, 2013)
Atrial fibrillation is a rapidly evolving epidemic associated with increased cardiovascular morbidity and mortality, and its prevalence has increased over the past few decades. In the past few years, the recent understanding of the diverse mechanisms of this arrhythmia has lead to the improvement of our therapeutic strategies. However, many clinicians have still felt the frustration in management of this commonly encountered arrhythmia. This book contains a spectrum of different topics from bench to bedside in atrial fibrillation. We strongly believe that scientists, cardiologists and electrophysiologists will find this book very informative and useful and the references cited in each chapter will definitely act as an additional source of information for readers.